Pemberdayaan Kelompok Tani dalam Pemanfaatan Janjang Kosong menjadi Kompos di Kampung Buatan Baru, Kecamatan Kerinci Kanan Kabupaten Siak Provinsi Riau - Sutikno, Agus; Zamaya, Yelly; Putri, Vivin Jenika; Pramana, Angga; Rahmah, Anania; AR, Nur Hasnah; Ruzain, Raihanatu Binqalbi (Unri Conference Series: Community Engagement, 2024)
The increasing area of oil palm plantations will increase the production of crude palm oil and empty fruit bunches. This will require chemical and non-chemical fertilisers. By reducing the use of excessive chemicals, sustainable and environmentally friendly oil palm plantations can be achieved. One way to achieve this is by utilising empty oil palm bunch waste into compost. This service aims to provide knowledge, understanding, and how to process empty oil palm bunches into compost. This activity was carried out in Riau Province, Siak Regency, Kampung Buatan Baru, Kerinci Kanan District. The goal achieved through this service is to increase community understanding and knowledge about the importance and benefits obtained from empty palm bunch waste into compost.